Agreement Between Clinical and Histopathological Diagnoses of Oral and Maxillofacial Lesions and Influencing Factors: A Five-Year Retrospective Study - Sindi AM; Aljohani K (Dove Medical Press, 2024)
Amal Mohammed Sindi, Khalid Aljohani Department of Oral Diagnostic Sciences, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Amal Mohammed Sindi, Department of Oral Diagnostic Sciences, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia, Email amsindi@kau.edu.saPurpose: Diagnosing oral and maxillofacial lesions is a multi-step, multidisciplinary process. If a clinical diagnosis is achievable, then a histopathological diagnosis is indicated to support and confirm the diagnosis. Histopathological examination of tissue biopsies is therefore an essential part of the diagnosis and/or treatment plan. The purpose of this study was to investigate the agreement between the clinical and histopathological diagnoses of oral and maxillofacial lesions and the patient, lesion, and healthcare provider factors that may affect this agreement.Patients and Methods: This was an observational, cross-sectional study of all patients who had been referred to the Oral Pathology Central Laboratory at the Faculty of Dentistry and University Dental Hospital at King Abdulaziz University in Jeddah, Saudi Arabia, between 2018 and 2022 for diagnosis of oral and maxillofacial lesions. Data extracted included information about the referring dental provider such as their clinical experience (number of years), specialty, certification, and education. Agreement between the clinical and histopathological diagnoses was evaluated, and logistic regression was used to assess provider characteristics associated with the accuracy of diagnosis.Results: The clinical and pathological diagnoses were concordant in 44.1% (n=378) of cases, and concordance was highest for odontogenic tumors (72.7%, n=24), significantly higher than for inflammatory lesions (37.3%, n=111). The anatomical locations with the highest diagnostic accuracy were the ventral surface of the tongue (71.4%, n=5), followed by the lips (52.6%, n=20). Patient age and sex and the dentist's years of experience were not associated with diagnostic agreement (p=0.2, p=0.9, and p=0.08, respectively). However, concordant diagnoses were significantly associated with the dentist's rank (p=0.02) and specialty (p=0.01). Clinical diagnoses made by oral surgeons at the time of biopsy were 1.6-times more likely (p=0.01) to agree with the pathological diagnosis compared with those made by other specialties when controlling for education, certification, and years of experience.Conclusion: These data are a reminder that a clinical diagnosis alone is not sufficient to secure the final diagnosis and to plan treatment. Histopathological examination remains essential for most oral and maxillofacial lesions.Keywords: dentist, oral diseases, clinical diagnosis, biopsy, histopathological diagnosis